Pengaruh Program Promosi Intervensi Cuci Tangan Pakai Sabun Terhadap Pengetahuan Siswa di Sekolah Dasar Jakarta - Lusi Endah Yuliani; Devi Angeliana Kusumaningtiar; CSP Wekadigunawan (HIGIENE: Jurnal Kesehatan Lingkungan, 2021)
Hand washing with soap is one of the sanitation measures by cleaning the hands and fingers using water and soap by humans to be clean and break the chain of germs. Washing hands with soap is also an effort to prevent disease.This study aims to analyze effect of hand washing with soap intervention promotion program on students' knowledge in jakarta elemntary schools. This type of research is quantitative using experimental research with one group pre-post test design. The sample in this study class V elementary Schools, amounting to 37 students. Data is collected by using a questionnaire. Counseling given by video and song washing media using hand soap. The statistical test used in this study is Wilcoxon. Based on the results it is known that there are significant differences between the value of prior knowledge and the value of knowledge after health promotion interventions. The difference in students' knowledge about washing hands with soap before and after the health promotion intervention was seen from an increase in score of 4.72 or an average difference of -4.714 with a p value of 0,000. There is an increase in the average number of respondents after receiving the educational instruction on washing hands with soap. Keywords : Hand washing, Knowledge, Health Promotion, Intervention